2005
DOI: 10.1203/01.pdr.0000187796.28007.2d
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Is Up-Regulated in Patients with Hypospadias

Abstract: Hypospadias is a congenital anomaly of the genitalia characterized by abnormalities of the urethra and foreskin, with the urethral meatus located in an abnormal position anywhere from the distal ventral penile shaft to the perineum. Because the incidence of hypospadias is approximately 1/200 -1/300 live male births, it is one of the most common congenital malformations, but its etiology is largely uncharacterized. Genomic analysis of hypospadic tissue indicated a potential role for activating transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…This effect may be due to disturbances on estrogenic responses during development (15,16,18). Moreover, ATF3 expression has also been reported to be up-regulated by the androgen receptor's activation by both androgens and estrogens in cell lines (27); this aspect indicate that variants in ATF3 may underlie androgenestrogen imbalances and influence the responsiveness to endocrine disrupters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may be due to disturbances on estrogenic responses during development (15,16,18). Moreover, ATF3 expression has also been reported to be up-regulated by the androgen receptor's activation by both androgens and estrogens in cell lines (27); this aspect indicate that variants in ATF3 may underlie androgenestrogen imbalances and influence the responsiveness to endocrine disrupters.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of estrogen-responsive genes has been documented in hypospadias (15,16). From these genes, the activating transcription factor 3 (ATF3), a member of the ATF/CREB family of transcription factors (17), has been the gene with the greatest up-regulation.…”
Section: Introductionmentioning
confidence: 99%
“…We also monitored expression of Atf3, a gene associated with hypospadias in humans and previously reported to have sexually dimorphic expression (31,32). Atf3 expression was not significantly different between males and females at prenatal stage E15.5, nor was it affected by testosterone or EB treatment at this stage ( Fig.…”
Section: Ar and Erα Show Dynamic Patterns Of Expression During Sexualmentioning
confidence: 93%
“…9 this latter finding emphasizes the risks associated with exposure to 'antiandrogenic' agents. studies from the past 10 years [63][64][65][66][67][68][69] have better defined the genes associated with hypospadias. a genome-wide association study of pooled Dna samples from 436 indivi duals with hypospadias and 494 without revealed a strong association between two common variants of diacylglycerol kinase κ (DGKK; rs1934179 and rs7063116).…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…expression studies in human urethral tissue have shown that ZEBI and ATF3 are especially promising candidates, owing to their known localization within the developing urethra. [68][69][70] Conclusive data regarding protein expression and function in human tissue are currently limited to a possible association of hypospadias with ATF3 overexpression 68 71 Further genetic studies are required in order to fully understand the basis of genetic s usceptibility to hypospadias.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%